2000
DOI: 10.1128/jvi.74.5.2178-2185.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Sequencing of Prototypic Human T-Lymphotropic Virus Type 1 (HTLV-1) from an HTLV-1/2 Seroindeterminate Patient

Abstract: Serological screening for human T-lymphotropic virus type 1 (HTLV-1) parallels the standard screening process for human immunodeficiency virus (HIV), in which samples found positive by enzyme-linked immunosorbent assay (ELISA) are confirmed with a modified Western blot procedure. There are a significant number of cases in which HTLV-1/2 ELISA-positive specimens demonstrate an incomplete banding pattern on this Western blot. Individuals providing these atypical antibody responses are categorized as seroindeterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
0
20
0
3
Order By: Relevance
“…However, a recent report has described the amplification of an HTLV-1 tax sequence from patients with neurological disease exhibiting an HGIP WB reactivity. This suggests that this seroindeterminate WB pattern might be associated in some rare cases with defective HTLV-1 strains or with a novel retrovirus having homology with HTLV-1, or finally with slowly replicating HTLV-1 (39,47). In addition, it seems unlikely that the HGIP may represent a delayed or slow seroconversion, because most of our followed-up subjects did not show any evolution of their WB profile over time and because the minority who did became EIA negative.…”
Section: Discussionmentioning
confidence: 88%
“…However, a recent report has described the amplification of an HTLV-1 tax sequence from patients with neurological disease exhibiting an HGIP WB reactivity. This suggests that this seroindeterminate WB pattern might be associated in some rare cases with defective HTLV-1 strains or with a novel retrovirus having homology with HTLV-1, or finally with slowly replicating HTLV-1 (39,47). In addition, it seems unlikely that the HGIP may represent a delayed or slow seroconversion, because most of our followed-up subjects did not show any evolution of their WB profile over time and because the minority who did became EIA negative.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have demonstrated that among low-risk BD even from endemic areas for HTLV-I/II infection exhibiting HGIP or Gag (p24) seroindeterminate patterns are unlikely to be infected with HTLV-I/II Busch et al, 2000;Rouet et al, 2001]. The HGIP profile was observed in a HAM/TSP case confirmed as HTLV-I positive by molecular diagnosis [Waziri et al, 2000]. In Martinique, neurological patients with chronic progressive myelopathies, but seronegative for HTLV-I, were further confirmed as HTLV-I positive by n-PCR [d 'Auriol et al, 1990].…”
Section: Introductionmentioning
confidence: 79%
“…In Martinique, neurological patients with chronic progressive myelopathies, but seronegative for HTLV-I, were further confirmed as HTLV-I positive by n-PCR [d 'Auriol et al, 1990]. Several studies have amplified HTLV-I tax sequences among seroindeterminate Gag samples from patients with neurological diseases or BD suggesting defective HTLV, novel retrovirus, or low proviral load [Waziri et al, 2000;Mangano et al, 2004].…”
Section: Introductionmentioning
confidence: 96%
“…It is also an important issue for comparative analysis between epidemiological studies performed in areas with low and high endemicity, especially in intertropical areas. The significance of these frequent indeterminate WB can be various but, in the majority of the cases, remains mostly unknown and a matter of discussion (24,28,57,69). Indeed, in rare cases, these patterns have been associated with (i) HTLV-1 but mostly HTLV-2 infection exhibiting an atypical HTLV serology (6,34,44,52,68,73,74), (ii) HTLV-1 seroconversion (17,45,46), and (iii) infection by a different HTLV, such as HTLV-3 or HTLV-4 (12,13,42,62,72).…”
mentioning
confidence: 99%